Antibodies against high‐risk human papillomavirus proteins as markers for invasive cervical cancer. Issue 10 (26th April 2014) - Combes, Jean‐Damien; Pawlita, Michael; Waterboer, Tim; Hammouda, Doudja; Rajkumar, Thangarajan; Vanhems, Philippe; Snijders, Peter; Herrero, Rolando; Franceschi, Silvia; Clifford, Gary
<x xml:space="preserve">Abstract</x> Different human papillomavirus (HPV) genes are expressed during the various phases of the HPV life cycle and may elicit immune responses in the process towards malignancy. To evaluate their association with cervical cancer, antibodies against proteins from HPV16 (L1, E1, E2, E4, E6 and E7) and HPV18/31/33/35/45/52/58 (L1, E6 and E7) were measured in serum of 307 invasive cervical cancer cases and 327 controls from Algeria and India. Antibody response was evaluated using a glutathione S‐transferase‐based multiplex serology assay and HPV DNA detected from exfoliated cervical cells using a GP5+/6+‐mediated PCR assay. Among HPV16 DNA‐positive cases, seroprevalence of HPV16 antibodies ranged from 16% for HPV16 E1 to 50% for HPV16 E6 and all were significantly higher than controls. Seroprevalence of E6, E7 and L1 antibodies for HPV18 and for at least one of HPV31/33/35/45/52/58 were also higher in cases positive for DNA of the corresponding type (50% and 30% for E6 of HPV18 and HPV31/33/35/45/52/58 combined, respectively). E6 and E7 antibodies were rarely found in controls, but cross‐reactivity was evident among cancer cases positive for DNA of closely phylogenetically‐related HPV types. E6 or E7 antibodies against any of the eight HPV types were detected in 66.1% of all cervical cancer cases, as compared to 10.1% of controls. E6, and to a lesser extent E7, antibodies appear to be specific markers of HPV‐related malignancy. However, even among cases positive for the same type of HPV DNA, approximately one‐third of cervical cancer cases show no detectable immune response to either E6 or E7.